Molasse-Alpine and Columbian - Eisbacher, G. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1974)
Summary Late-orogenic sediments deposited alongside growing mountain belts reflect the rise and cooling of crystalline complexes within the core zone of the orogens. The nature of these molasse deposits is strongly influenced by structures adjacent to the sedimentary basins. Despite differences in scale and paleoclimate the molasse of the Alps and that of the Columbian Orogen show remarkable similarities.